Synthesis and biological properties of Zinc(II) complexes of some 2-hydroxyacetophenone-benzoylhydrazones - Ali, Hapipah Mohd; Teoh, H.L.; Abdullah, N.; Ismail, E.; Basirun, Wan Jefrey; Zain, S.M.; Subramaniam, P.; Nadiah Abdul Halim, S. (Faculty of Science, University of Malaya, 2006)
The new zinc(II) complexes have been prepared in ethanol by condensation of 2-hydroxyacetophenone with either benzhydrazide or 3-methoxybenzhydrazide and zinc acetate in the presence of triethylamine. The IR, 1H, 13C NMR and UV-visible data show coordination of hydrazone ligands to the metal centers and the spectroscopic data augur well with the x-ray structures which had been published earlier. The Schiff bases and their complexes were screened for antimicrobial, cytotoxic and antioxidant activities. The anti-microbial activities of the ligands and complexes were evaluated by using plate diffusion method against some gram-positive bacteria, gram-negative bacteria and two fungi. There was growth inhibition exhibited by ligands and zinc(II) complexes against tested bacteria and fungi. The Schiff base, H 2hapbh was cytotoxic with IC 50 10-0 μgml -1 against the MCF-7 (human breast cancer cells) while both zinc(II) dimer complexes were strongly cytotoxic with IC 50 values of 4.5 μgml -1. The Schiff bases and zinc(II) complexes showed higher antioxidant activity than quercetin or vitamin E and is comparable with butylated hydroxytoluene (BHT), a commercially used synthetic antioxidant.